Human resource diversity management (HRDM) practices as a coping mechanism for xenophobia at transnational workplace: A case of a multi-billion-dollar economic corridor - Umer Zaman (Taylor & Francis Group, 2021)
China–Pakistan Economic Corridor (CPEC), a multibillion-dollar partnered project is considered as a game-changer, as it combines the strategic interests of China and Pakistan that cannot be compromised. The mega-construction project has recently experienced xenophobic incidents involving Chinese and Pakistani nationals, creating significant harm towards the CPEC progress and success, especially under enormous geopolitical and economic threats. This sketches our motivation for conducting this research that focused on qualitative design based expert interviews of 8 individuals (i.e., both Chinese and Pakistani nationals) directly associated with CPEC. Drawing on a review of mainstream research, the article constructs a framework to explore the demotions of xenophobic behaviors at workplace and to explore the human resource diversity management (HRDM) practices (including intercultural training and development, flexible compensation, international staffing, work-design, and work–life balance) in coping with xenophobia and its sub-dimensions (including discrimination, prejudice, and stereotyping). Experts based interview findings confirm the presence of xenophobia in the CPEC. We propose a framework of various HRDM practices in managing the xenophobia at workplace, however, it is still in its infancy stage. Hence, the present study introduces a new operating model for future researchers, academicians, and management practitioners to cope with xenophobia based on the practices and insights that were explored during this research.